Integrated Protein–Protein Interaction and Weighted Gene Co-expression Network Analysis Uncover Three Key Genes in Hepatoblastoma - Tian, Linlin; Chen, Tong; Lu, Jiaju; Yan, Jianguo; Zhang, Yuting; Qin, Peifang; Ding, Sentai; Zhou, Yali (Frontiers in Cell and Developmental Biology, 2021)
Hepatoblastoma (HB) is the most common liver tumor in the pediatric population, and outcomes for advanced-stage or chemotherapy-refractory HB patients remain dismal. The objective of this study was to find key genes in HB through integrated microarray analysis and subsequent experimental validation. Based on two microarray datasets (GSE131329, and GSE75271), 856 differentially expressed genes (DEGs) between HB and normal liver tissues were identified after data merging and batch effect correcting. Then, protein-protein interaction (PPI) analysis and weighted gene co-expression network analysis (WGCNA) were conducted to explore HB-related critical modules and hub genes. Subsequently, Gene Ontology (GO) analysis revealed critical biological functions in the initiation and progression of HB. Kyoto Encyclopedia of Genes (KEGG) analysis showed cell cycle phase transition and the PI3K/AKT signaling in association with HB growth. Then, hub genes from PPI and WGCNA analyses were intersected, and 5 candidate genes left. Eventually, receiver-operator-characteristic curve (ROC) analysis and literature search were utilized, and CCNA2, CDK1 and CDC20 were identified as key genes. Subsequent experimental validation demonstrated that knockdown of CCNA2, CDK1 or CDC20 inhibited aggressive biological behaviors of both HepG2 and HuH-6 cell lines in vitro. In conclusion, we identified CCNA2, CDK1 and CDC20 as new therapeutic biomarkers for HB, providing novel insights into important and viable targets in future HB treatment.